(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The origin of human habitation is from rural areas. According to Paul (2022), “Rural settlements are the spatial carriers of rural multifunctionality and various problems related to living conditions are the main manifestations and causes of unbalanced and inadequate rural development”. The intensity of rural settlements is higher in areas where infrastructure is developed. Also, in the rural areas where the intensity is high, agriculture and ancillary businesses are carried out on a large scale. In the present research paper intensity of rural settlements in Aurangabad district has been studied.